Status Epilepticus Following Electroconvulsive Therapy - Omprakash, T. M. (Medknow Publications & Media Pvt Ltd, 2013)
Electro convulsive therapy (ECT) induced status epilepticus is known to occur in patients undergoing ECT. Its recognition and management under general anesthesia are of paramount importance; otherwise it may endanger the life of the individual.